2018
DOI: 10.1128/aem.01902-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Enterococci Isolated from Retail Meats in the United States, 2002 to 2014

Abstract: Bacteria of the genus are important human pathogens that are frequently resistant to a number of clinically important antibiotics. They are also used as markers of animal fecal contamination of human foods and are employed as sentinel organisms for tracking trends in resistance to antimicrobials with Gram-positive activity. As part of the National Antimicrobial Resistance Monitoring System (NARMS), we evaluated several retail meat commodities for the presence of enterococci from 2002 to 2014, and we found 92.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 28 publications
5
63
2
Order By: Relevance
“…Lower prevalences have been reported from Tunisia (19) and Greece (12) In our study, the most prevalent species were determined as E. faecalis, followed by E. faecium, E. durans, E. gallinarum and E. casseliflavus. Similar preponderances from chicken meat samples have been reported previously from Tunisia (19), Brazil (8), USA (25), in contrast, some other studies from Scandinavia, Spain and Italy (6), Greece (12), E. faecium was stated as of the preponderant species. Varieties of preponderances can be linked with geographical diversities or typing techniques (14,21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lower prevalences have been reported from Tunisia (19) and Greece (12) In our study, the most prevalent species were determined as E. faecalis, followed by E. faecium, E. durans, E. gallinarum and E. casseliflavus. Similar preponderances from chicken meat samples have been reported previously from Tunisia (19), Brazil (8), USA (25), in contrast, some other studies from Scandinavia, Spain and Italy (6), Greece (12), E. faecium was stated as of the preponderant species. Varieties of preponderances can be linked with geographical diversities or typing techniques (14,21).…”
Section: Discussionsupporting
confidence: 89%
“…In our study 90% (18/20) of the VRE isolates were intermediate or resistant to linezolid and it also provides an alarming warning about treatment of VRE infections. As part of the NARMS (National Antimicrobial Resistance Monitoring System), Tyson et al (25) evaluated several retail meat commodities from 2002 to 2014, and found 92% of enterococci contamination. According to their study, none of the isolates was resistant to vancomycin, but only one isolate was resistant to linezolid, and resistance to tigecycline was below 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Enterococcus, which includes presently about 40 recognized species, were initially classified as group D streptococci sharing several phenotypic and biochemical similarities, making their identification difficult (Yost et al, 2011). Enterococci have been proposed as fecal indicator bacteria for microbial source tracking (Byappanahalli et al, 2012;Boehm and Sassoubre, 2014) and are often used in tracking trends in resistance to antimicrobials for various resistance surveillance systems (Tyson et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…27 Tyson et al in a study on antimicrobial resistance of enterococci isolated from meats in the United States, 2002-2014, reported a multiple drug resistance pattern of the isolates to antibiotics such as erythromycin, gentamicin and tetracycline. 28 Furlaneto-Maia et al reported a high rate of enterococcal resistance to erythromycin (86.7%), vancomycin (80.0%), tetracycline (43.35) and gentamicin (33.3%) in Brazil. 29 Bacterial antibiotic resistance has become an urgent health problem worldwide.…”
Section: Discussionmentioning
confidence: 99%